Eight challenges of servitisation for the configuration, measurement and management of organisations. Issue 6 (14th November 2016) - Nudurupati, Sai S.; Lascelles, David; Wright, Gillian; Yip, Nick
Abstract : Purpose: There is an extensive research literature on servitisation and the related field of product-service systems that has emerged independently from different fields including engineering, management, design and environmental studies. The purpose of this paper is to conduct a structured literature review to explore, identify and synthesise the multi-disciplinary research challenges in the journey towards servitisation. Design/methodology/approach: The research approach is a systematic literature review using key word searches and citation tracking for research reported between 1990 and 2013 in research databases that cover the fields which have generated the body of knowledge. Findings: One of the key findings from the extant literature on servitisation is that it suffers from three fundamental weaknesses. First, numerous studies are conceptual in nature with limited practicality. Second, there are relatively few empirical studies, and often the findings relate to a single case study based on the insights of a limited number of senior managers. Third, often the dynamics are insufficiently studied in these organisations because data for most cases are collected post-event. Research limitations/implications: Based on the literature review and its shortfalls, this paper proposes a holistic framework of eight themes that require further attention from academic researchers in order that a more complete conceptual understanding of servitisation is developed to support practice. Practical implications: Each theme in the framework has an associated list of questions that can be addressed through research and presented to managers as a challenge agenda to improve their servitisation efforts. That servitisation is associated with differentiation and competitive advantage makes this a valuable approach for managing corporate performance. Originality/value: Research from multi-disciplinary sources is synergised in order to develop an overarching servitisation agenda that transcends domain-based boundaries. This paves the way for an approach to servitisation that is coherent and harmonious.